Speaker stance and engagement across disciplines in Lithuanian university lectures: the case of mes ‘we’ in medicine and business administration - Maslauskienė, Greta (Taikomoji kalbotyra, 2023)
To gain a greater understanding of how speakers construct their disciplinary-situated identities and interact with their addressee(s) in Lithuanian spoken academic discourse, this corpus-based exploratory analysis focuses on the use of mes ‘we’ as a marker of stance and engagement in lecturers’ speech in Lithuanian university lectures on business administration and medicine. The data reveals that the lecturers in business administration used only the inclusive mes ‘we’, which is known to promote student involvement and strengthen lecturer-student rapport. The instructors in medicine frequently employed the exclusive reference to indicate their belonging to professional communities and highlight their level of expertise in the discipline, creating a sense of distance between the lecturer and the student audience.